PENGARUH KONSENTRASI GARAM TERHADAP KADAR PROTEIN TELUR ASIN PADA KELURAHAN TUNGGAKJATI - Lina Aliyani Mardiana (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Duck eggs as a food that is quite perfect contains high nutrients that are easily digested, rich in protein, fat and other substances that the body needs. The protein content in duck eggs is quite high, at 13.1 grams per 100 grams compared to 12.8 grams in chicken eggs. Duck eggs are perishable. One way to overcome this problem is by preservation, namely the dry method (ash and salt). This study aims to determine the effect of salt concentration on the protein content of duck eggs. The approach used in this study is a quantitative approach and the type of experimental research using a completely randomized design (CRD) pattern consisting of 5 treatments and 4 replications. The treatments consisted of P0 (ash concentration 60 grams: salt 0 grams), P1 (ash concentration 60 grams: salt 20 grams), P2 (ash concentration 60 grams: salt 40 grams), P3 (ash concentration 60 grams: salt 60 grams) , and P4 (60 grams of ash concentration: 80 grams of salt). The data of this study were sourced from the results of the protein content and organoleptic quality test of salted eggs. Data collection for protein content was carried out by testing the protein content of duck eggs that had been given salt with different concentrations. The results showed that based on the graph of the highest protein content in the P2 treatment with a mean score of 14.23%, the conclusion of this study showed that different salt concentrations had no effect on the protein content of duck eggs.